(untitled) (Mustansiria Dental Journal, 2018)
Aim: Dental decay is a process in which the hard mineral structure of teeth is dissolved. The process produces a cavity on the crown of the tooth or a softening of the root surface. Without regular dental care people are often unaware of the condition, whereas those who usually seek dental care for a check-up are more likely to have dental decay treated in a timely manner The aim of the present study was to determine the caries experience of public dental patients by age, sex with the type of dental visit and brushing behavior in adults in Tikrit city, Iraq. Subjects and methods: A sample of 1284 individuals(580 males and 704 females)with an age range of (18-60 years) attending the teaching dental hospital of collage of dentistry of Tikrit university and the specialized dental center , were examined according to WHO guidelines using DMFT index. Questionnaires were used to assess the level of dental health attitude among the individuals. Results: The distribution of patients was high at younger age for both sexes. Emergency visit had a higher percentage of patients (82.2%). 63.6% of the patients brush their teeth two or more. The mean DMFT scores were 7.5 (8.3 for female and 6.7 for male). Mean DMFT for both sex increases with age. The percentage of decayed teeth (D/DMFT%) was the highest among younger age group (60.7% for female and 63.1% for male). There was statistically a highly significant difference between age, sex, dental visit type and brushing behavior and DMFT. Emergency patient did show higher level of decayed and missing teeth while general patient did show higher level of filled teeth. Emergency dental visit had higher percentage of decayed teeth (57.3%) than general dental visit (42.5%). One or less brushing patient had higher level of decayed and missing teeth, while two or more brushing patient show higher level of filled teeth. The percentage of decayed teeth for one or less brushing patients was (62.9%) higher than two or more brushing patients (50.1%). Conclusion: It was concluded that the present study findings for DMFT scores was higher than the global standers according to the world health organization (WHO). Therefore, there is a great need to combine restorative-oriented dental services with preventive- oriented dental services in order to improve the oral health status of this population.